2022
DOI: 10.3892/etm.2022.11691
|View full text |Cite
|
Sign up to set email alerts
|

Nypa fruticans Wurmb inhibits melanogenesis in isobutylmethylxanthine‑treated melanoma via the PI3K/AKT/mTOR/CREB and MAPK signaling pathways

Abstract: Malignant melanoma is responsible for 3.0 and 1.7% of cases of tumor incidence and tumor-associated mortality, respectively, in the Caucasian population. Melanoma is a type of skin cancer that occurs when melanocytes mutate and divide uncontrollably. Nypa fruticans Wurmb (NF) is abundant in phytochemicals (polyphenols and flavonoids) and is traditionally used to treat diseases of the respiratory tract. The present study investigated the inhibitory effect of the ethyl acetate fraction of NF (ENF) on melanogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It has been reported that the activation of the protein kinase AKT mediates the phosphorylation of GSK-3β, which induces melanin synthesis via the upregulation of MITF. In other words, blocking the phosphorylation of AKT triggers the process of melanogenesis [ 17 ]. To investigate whether 7H-4M induces melanogenesis through the AKT signaling pathway in B16-F10 cells, we conducted experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the activation of the protein kinase AKT mediates the phosphorylation of GSK-3β, which induces melanin synthesis via the upregulation of MITF. In other words, blocking the phosphorylation of AKT triggers the process of melanogenesis [ 17 ]. To investigate whether 7H-4M induces melanogenesis through the AKT signaling pathway in B16-F10 cells, we conducted experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Melanogenic factors are influenced by external stressors and are regulated through cross-regulation involving various signaling molecules. The cAMP signaling pathway has been reported as a regulator of melanogenesis, particularly through the cAMP/PKA/CREB pathway, which activates the expression of genes related to melanogenesis, including MITF, tyrosinase, TRP-1, and TRP-2 [ 17 , 18 ]. In this study, syringetin was found to significantly enhance PKA activity ( Figure 3 ), suggesting that the melanogenic effect of syringetin is mediated via the cAMP/PKA/CREB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…cAMP is a crucial signal transduction molecule that activates the phosphorylation of PKA, which is one of the primary pathways that stimulates melanogenesis in response to extracellular stimuli. PKA activation then initiates two distinct signaling pathways that upregulate MITF expression: CREB and GSK3 [17,18]. Therefore to investigate the transcription factor that stimulates MITF expression, we examined the phosphorylation levels of PKA, which is the downstream activator of cAMP signaling Figure 3 shows that syringetin treatment significantly upregulated the expression level of phosphorylated PKA in comparison to the control treatment.…”
Section: Syringetin Induced Melanogenesis In B16f10 Cells Through The...mentioning
confidence: 99%
See 1 more Smart Citation